ORTHODONTIC-SURGICAL THERAPY OF THE IMPACTED CENTRAL MAXILLARY INCISOR: A CASE REPORT - Mitić, Vladimir; Todorović, Kosta; Mitić, Aleksandar (Acta medicae Medianae, 2023)
The aim of this study was to clearly determine the possibility of treatment of impacted central incisor liberation in a 9-year-old girl, and then to bring the tooth to its natural place in the dentition in the shortest possible time interval. The paper presents the liberation of the impacted central incisor in a 9-year-old girl. Prior to the intervention, a detailed examination (CBCT) and analysis of all parameters were performed in order to determine the possibility of successful therapy of the impacted tooth. The orthodontic treatment plan included three steps—creation of space, exposure of crown, and forced eruption. After the surgical intervention of releasing the impacted central incisor, a button with a modified direct bonding method was placed in the same act, with a twisted wire by an orthodontist, and after removing the floss, the tooth was pulled with a fixed orthodontic appliance (SWA technique). Follow-ups were done every two weeks until the appearance of teeth in the mouth.The modified method of direct bonding of the button for the surface of the impacted tooth proved to be easier, compared to the conventional method. A quality diagnosis with an adequate multidisciplinary therapy gives a satisfactory result in the optimal time.A multidisciplinary diagnosis and therapy are becoming more and more present in dentistry, and the order of therapy should be taken into account.
Keywords: tooth impaction, closed flap, direct bonding, CBCT